Service Relationship With Customer Satisfaction PT. Bank Rakyat Indonesia (Persero) Tbk Bengkulu Branch - Herman Herman; Salehan Salehan (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the relationship between service and customer satisfaction of PT. Bank Rakyat Indonesia (Persero) Tbk Bengkulu Branch. The design used is Spearman Rank Correlation. The population is the average number of current account customers of PT. Bank Rakyat Bengkulu (Persero) Tbk Bengkulu Branch who transacted within one week amounted to 60 people, while the research sample consisted of 30 people calculated using the Notoatmojo formula and selected using a simple purposive technique. Using primary data by distributing questionnaires to current account customers who are transacting at PT. Bank Rakyat Indonesia (Persero) Tbk Bengkulu Branch, analyzed using Sperman Rank Correlation. The results showed that the calculated rho value was greater than the table rho value (0.520 > 0.478) at an error level of 1% and n = 30. The conclusion of the study was that there was a positive and significant relationship between service and customer satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk Bengkulu Branch.